Highly red luminescent stabilized tetragonal rare earth-doped HfO2 crystalline ceramics prepared by sol-gel - Borges, Fernanda Hediger; da Hora Oliveira, Douglas Silva; Hernandes, Giulia Paulino; Lima Ribeiro, Sidney José [UNESP]; Gonçalves, Rogéria Rocha (Elsevier, 2022)
We report high incorporation of rare earth ions (RE3+) into hafnia nanoparticles prepared by the sol–gel method and investigate how these dopants affect hafnia structure and phase transformation. An ethanolic suspension containing 5-nm hafnia nanoparticles was obtained from HfOCl2.8H2O in ethanol. Pure and 0.1–7 mol% Eu3+-doped materials afforded HfO2 monoclinic phase, whereas hafnia nanoparticles added with 10 and 20 mol% Eu3+ were stabilized in the tetragonal phase. Structural evolution of the nanoparticles was analyzed by Eu3+ luminescence spectroscopy and excited level lifetimes. The emission spectra in the visible region showed an increase of the Eu3+ site symmetry due to hafnia phase transformation from monoclinic to tetragonal upon increasing Eu3+ concentration. Concentration quenching, followed by lifetime measurements, occurred at high Eu3+ concentration (20 mol %). The hafnia tetragonal phase was stabilized with non-optically active La3+ (a fixed concentration of 10 mol %), co-doped with a lower concentration of Eu3+ ions (from 0.1 to 3 mol %). This strategy ensured that Eu3+ luminescence in tetragonal hafnia was intense and prevented quenching by the high Eu3+ concentration. In this sense, the hafnia structure and emission properties can be tailored by the RE3+ concentration, so that an interesting material for applications in photonics and biophotonics can be achieved.